Exploring the Need for Differentiated Instruction Frameworks in Enhancing 21st Century Skills in Mathematics Education - Setambah, Mohd Afifi Bahurudin; Ariffin, Azli; Zaini, Syaza Hazwani; Jaafar, Anis Norma Mohamad; Negara, Habibi Ratu Perwira; Hanazono, Hayato (Journal of Management World, 2025)
This study aims to explore the need to develop a 21st century knowledge and skills framework based on differentiated instruction, especially in mathematics education. This study uses a cross-sectional survey design by combining quantitative and qualitative data. 100 mathematics teachers from various schools in Malaysia were selected with certain criteria to be used as a study sample. While 3 teachers among the teachers were interviewed to obtain their views in depth. The study findings show that teachers have basic knowledge of differentiated instruction, but they are not confident in implementing it in mathematics teaching, especially in applying 21st century knowledge and skills. The findings show that there is a high need to develop a 21st century knowledge and skills framework based on differentiated instruction for mathematics education. This study is expected to have implications for improving teachers' skills in teaching mathematics, supporting the curriculum and strengthening students' soft skills.